1962
DOI: 10.1021/jo01056a006
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Amicetin

Abstract: Methanolysia of amicetin (I) yielded, besides cytimidine (II),*sa the methyl glycosides (VI) of a neutral sugar, amicetose (VII), and of an amino sugar, amoaamine (IX). Periodate fission of the 2,4-dinitrophenylhydrazone of amicetose (VIII) gave acetaldehyde and a derivative of succindialdehyde, leading to structure VI1 for the neutral sugar. Various degradations of amosamine and its derivatives were conducted and the results showed the amino mgar to be IX. Evidence is presented for the mode of linkage of amos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 1 publication
3
27
0
Order By: Relevance
“…Reduction of (95) with sodium borohydride gave methyl 3,4-di-0acetyl-2,6-dideoxy-a-~-arab~no-hexopyranoside (97) 52 which was saponified to give the alcohol (98).52-55 Selective reaction with 9-toluenesulphonyl chloride afforded the 3-$-toluenesulphonate (99) 56 which on treatment with sodium azide gave a moderate yield of the azide (100) Reductive formylation of (100) gave methyl 2,3,6-t rideoxy-3-dimet hylamino-a-L-ribo-hexopyraposide (methyl L-megosaminide) (37) which was identical with the natural material. In a similar manner the panomer (101) 52 prepared by sodium borohydride reduction of (96) was converted into alcohol (102) 52954 which was then selectively reacted with $-toluenesulphonyl chloride to give (103).54 The latter was converted into the azide (104) 54*57 which on reductive formylation gave methyl p-L-megosaminide (38) which was identical with the natural sample.…”
Section: And Discussionmentioning
confidence: 99%
“…Reduction of (95) with sodium borohydride gave methyl 3,4-di-0acetyl-2,6-dideoxy-a-~-arab~no-hexopyranoside (97) 52 which was saponified to give the alcohol (98).52-55 Selective reaction with 9-toluenesulphonyl chloride afforded the 3-$-toluenesulphonate (99) 56 which on treatment with sodium azide gave a moderate yield of the azide (100) Reductive formylation of (100) gave methyl 2,3,6-t rideoxy-3-dimet hylamino-a-L-ribo-hexopyraposide (methyl L-megosaminide) (37) which was identical with the natural material. In a similar manner the panomer (101) 52 prepared by sodium borohydride reduction of (96) was converted into alcohol (102) 52954 which was then selectively reacted with $-toluenesulphonyl chloride to give (103).54 The latter was converted into the azide (104) 54*57 which on reductive formylation gave methyl p-L-megosaminide (38) which was identical with the natural sample.…”
Section: And Discussionmentioning
confidence: 99%
“…The chemical structure of amicetin was established in 1962 after extensive studies of its hydrolytic products (22,56) and was finally confirmed by crystallization studies (55). From various actinobacterial strains, a group of 10 amicetin analogues had been isolated, including bamicetin (compound 2) and plicacetin (compound 3) (31), norplicacetin (compound 4) (21), oxamicetin (42), SF2457 (37), oxyplicacetin (11), and cytosaminomycins A to D (30).…”
mentioning
confidence: 99%
“…30 The titration data revealed the pK a s for the two ionising residues to be 7.52 (tertiary amino N(I)) and 7.27 (primary amino NH 2 (VI)), which agree well with the data based on other methods reported in the literature. 3,4 Successful measurement of the pK a s also simultaneously provided additional evidence for the assignment of the proton resonances H1, H2, H19a and H19b, as described in the preceding section.…”
Section: Nmr Ph Titration Of Amicetinmentioning
confidence: 78%
“…1,2 Following fermentation growth and butanol solvent extraction, amicetin was isolated as a pure crystalline product and its chemical structure was solved by analysis of hydrolytic products. 3,4 Amicetin belongs to a family of nucleoside antibiotics containing a hexose-cytosine moiety ( Fig. 1) and functions as a peptidyl transferase RNA inhibitor by blocking protein biosynthesis within the cell.…”
Section: Introductionmentioning
confidence: 99%